2018
DOI: 10.1088/1674-1137/42/8/083101
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy and decay properties of charmonium

Abstract: The mass spectra of charmonium are investigated using a Coulomb plus linear (Cornell) potential. Gaussian wave function in position space as well as in momentum space are employed to calculate the expectation value of potential and kinetic energy respectively. Various experimental states (X(4660)(5 3 S1), X(3872)(2 3 P1), X(3900)(2 1 P1), X(3915)(2 3 P0) and X(4274)(3 3 P1) etc.) are assigned as charmonium states. We also study the Regge trajectories, pseudoscalar and vector decay constants, the Electric and M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 178 publications
4
37
0
Order By: Relevance
“…Thus, the above findings, Eqs. (71) and (72), reinforce our conclusion obtained in the f V case that the replacement M → M 0 is required to give self-consistent results for the decay constants in both the CLF and the SLF quark model.…”
Section: Decay Constants Of 1 a And 3 A Mesonssupporting
confidence: 85%
“…Thus, the above findings, Eqs. (71) and (72), reinforce our conclusion obtained in the f V case that the replacement M → M 0 is required to give self-consistent results for the decay constants in both the CLF and the SLF quark model.…”
Section: Decay Constants Of 1 a And 3 A Mesonssupporting
confidence: 85%
“…The same interpretation for the X (4274) was proposed in Ref. [97]. In a study of heavy quarkonium hybrids based on the strong coupling regime of pNRQCD [98], the authors found out that the X (4274) is compatible with a χ c1 (3P) state, which may be affected by the D * + s D * − s threshold.…”
Section: (4274): Other Interpretationssupporting
confidence: 63%
“…The Hamiltonian matrix was constructed and diagonalised to obtain the masses and wavefunctions of charmonium states. In Table 2, we compare the masses of radially and orbitally excited c c states with experiment [6] and other theoretical predictions [7,10,[59][60][61][62]. Authors in refs.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Authors in refs. [7,[59][60][61][62] have also used Cornell type potential to study the c c system, where as in ref. [10], authors use a screened potential.…”
Section: Discussion and Summarymentioning
confidence: 99%